Comparative EvaluationIn vitroof the HerbicideFlurochloridone by Cytokinesis-blockMicronucleus Cytome and Comet Assays - Nikoloff, Noelia (2014)
Thein-vitroeffects of flurochloridone and its formulations Twin Pack Gold1(25% a.i.) andRainbow1(25% a.i.) were evaluated in Chinese Hamster Ovary K1 (CHO-K1) cells. The cytokinesis-blockmicronucleus cytome (CBMN-cyt) and single-cell gel electrophoresis (SCGE) assays were used. Theactivities were tested within the range of final concentrations of 0.25–15lg flurochloridone/mL. Theresults demonstrated that both the flurochloridone and Rainbow1were not able to induce micronuclei(MN). On the other hand, Twin Pack Gold1only increased the frequency of MN at 5lg/mL. Furthermore,10 and 15lg/mL of both formulations resulted in a cellular cytotoxicity demonstrated by alterations in thenuclear division index and cellular death. SCGE assay appeared to be a more sensitive bioassay fordetecting primary DNA strand breaks at lower concentrations of flurochloridone than MN did. A markedincrease in the genetic damage index was observed when 5 and 15lg/mL of both flurochloridone andRainbow1but only when 15lg/mL of Twin Pack Gold1were used. This is the first report demonstratingthat flurochloridone and its two commercial formulations are able to induce single-strand DNA breaksinvitroon mammalian cells.